Integrating handover curricula in medical school. (3rd July 2020) - Sheng, Jim; Manjunath, Sonakshi; Michael, Meghan; Gajera, Prakash; Wang, Eric; Sendelbach, Dorothy; Greilich, Philip; Ambardekar, Aditee
Summary: Background: Transitions of care are a patient‐safety priority. Constructs such as SBAR (situation, background, assessment, recommendation) and I‐PASS (illness severity, patient summary, action list, situation awareness, synthesis by receiver) have been used to teach the benefit of structured handovers and have demonstrated an impact in simulated and clinical environments. Despite this, there is still a lack of literature describing handover training for medical students that allows early and sustained knowledge and skill acquisition. Methods: We designed a curriculum to teach handovers to medical students that spanned 28 months of a 4‐year medical education curriculum at a large medical school. The curriculum included two separate workshops that book‐ended medical student core clerkships. The curriculum was evaluated via knowledge‐based surveys and open‐ended feedback from students. Results: Two‐hundred and forty students participated in the first 'Transition to clerkship' (T2C) workshop. There was improvement in the mean scores on a knowledge‐based survey after the workshop (p < 0.001). The overall improvement in performance remained significant 1 year later (p < 0.001). Following the second, 'Residency essentials' (RE) workshop, students demonstrated marginal improvement in knowledge when compared with scores immediately post‐T2C and pre‐RE. There was overall improvement from pre‐T2C to post RE. Discussion: We outline the design and facilitation of two workshops for a large medical school class, as book‐ended curricula before and after the clerkship phase of education. This project highlights the need for targeted learning and practice in handover delivery during clinical rotations to maintain and continually improve skills. We describe vertically integrated curricula that are logistically plausible, meaningful and beneficial.